Effect of herbo-mineral formulation (Shilajatu Rasayana) in letrozole-induced polycystic ovarian syndrome - Vanitha Hosur Kumari; Revanasiddappa S Sarashetti; Kashinath S Hadimur; Kasturi A Patil (Wolters Kluwer Medknow Publications, 2016)
The major cause of female infertility in recent years is polycystic ovarian syndrome commonly called as PCOS, compared to yonivyapath (disorders of female reproductive system) described in Ayurveda. Shilajatu Rasayana herbo-mineral preparation mentioned in "Rasendra Chudamani" indicated in yonyaamaya (disorders of female reproductive system), gulma (tumors), meha (hyperinsulinemia), pandu (anemia), etc. is expected to contribute positive and better result in letrozole-induced PCOS, considering the previous analytical and experimental studies. Letrozole, Shilajatu Rasayana, clomiphene citrate, ghee, and female albino rats formed the materials for the study. Totally thirty female rats were initially induced to develop PCOS by injecting letrozole. The induction of PCOS in rats was checked through vaginal smear analysis and further confirmed by hormonal assay. PCOS-induced rats were treated with clomiphene citrate (standard), Shilajatu Rasayana (test drug), and ghee (control). Ovarian and uterine weight, hormonal assay, and histomorphometric changes were observed and recorded. Shilajatu Rasayana has shown a significant result in letrozole-induced PCOS by regulating hormones, reduction of cystic follicles, maturation of ovarian follicles, and decreasing the increased ovarian and uterine weight.